Improving Operating System Availability With Dynamic Update - Baumann, Andrew; Appavoo, Jonathan; Silva, Dilma Da; Krieger, Orran; Wisniewski, Robert W. (Proceedings of the Workshop on Operating System and Architectural Support for the On-Demand IT Infrastructure, 2004)
Dynamic update is a mechanism that allows software updates and patches to be applied without loss of service or down-time. Dynamic update of an operating system enables administrators to defer rebooting or restarting services and the resultant disruption, without trading off the ability to apply important security fixes or improve functionality and performance through software updates. We have considered the problem of building a dynamically updatable operating system, and have designed and implemented a prototype update mechanism for the K42 research operating system. Although the prototype utilises the hot-swapping features of K42, many aspects of the design would be relevant for other operating systems. In this paper we categorise and discuss these issues, and where possible propose solutions. We also describe our current prototype.